Professional development: a mixed methods study of Masters of Public Health alumni - Baron-Epel, Orna; Douvdevany, Yana; Ivancovsky-Wajcman, Dana; Barach, Paul; Bashkin, Osnat; Czabanowska, Katarzyna; Dopelt, Keren; Davidovitch, Nadav; Jakubowski, Szczepan; MacLeod, Fiona; Malowany, Maureen; Okenwa-Emegwa, Leah; et al. (Frontiers in Public Health, 2024)
Introduction We examined the perceptions of the Master of Public Health (MPH) degree graduates regarding their personal competencies, job performance and professional development using a mixed method, explanatory sequential design. Methods A cross-sectional, self-administered questionnaire of the Haifa School of Public Health alumni who graduated between 2005 and 2022 was disseminated to 849 graduates between March and June 2022, from which 127 responded (response rate: 14.90%). This was followed by 24 in-depth interviews with alumni from the same sample (conducted between November 2022 and March 2023). Results The sample included 74.8% of females with a mean age of 40.7 years, 35% of alumni agreed that the MPH degree helped them attain a promotion in their present position (in rank or salary), and 63.8% felt that the degree helped them improve their job performance and contribute to their current workplace. Most (80.3%) alumni reported not changing jobs after graduation. The interview themes revealed that the MPH contributed to their personal and professional lives, provided them with a holistic view of public health and health systems, and improved their in-depth scientific skills. The main reported barriers to professional development included missing core competencies, low salaries, and a lack of information regarding suitable jobs. Surprisingly, an MPH was not a requirement for some public health sector jobs. Alumni reported that the MPH degree contributed to improving many graduates’ careers and satisfaction levels and to build their leadership competencies in public health. Discussion There seems to be a lack of coordination between the academic curriculum and the jobs available for alumni, hindering better alumni professional development. Regular discussions, information sharing, and curriculum refinements between MPH program leaders and health sector leaders might help address many of the concerns of MPH degree graduates.